Ekologisk landskapsplan för fastigheten Götebo 1:5 - Andersson, Jenny (2008)
This thesis constitutes a long term (100 year) ecological landscape management plan for the estate Götebo 1:5. The estate is situated close to Gothenburg and is owned by Skogssällskapet. The planning has been made by dividing the estate into different areas (zones). In each zone one of the goals nature conservation, recreation or economical yield has been prioritized. Nature conservation is one of the main goals for the forest management plan. The base for the planning of nature conservation is a literature study where threshold values for different aspects of nature conservation is discussed. Examples of goals for conservation that are set in the literature study are how big the amount of dead wood and how large the proportion of deciduous trees should be on the estate. The planning for recreation has foremost been done by proposing which walking and horse-back riding tracks that needs improvement to make the estate more attractive for visitors. Forest management for recreation has been exemplified in a literature study about recreation forests. The literature study can be used as basic data for decision-making regarding forest management in the recreational forest areas. The economical result for the forest management proposed in the plan is also presented and put in relation to the economical results that other forms of forest management would lead to. Key words: nature conservation, planning, recreation, zoning